1981
DOI: 10.1056/nejm198109103051103
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin H Disease and Mental Retardation

Abstract: Each of three families of northern European origin contains a mentally retarded son with hemoglobin H (Hb H) disease. One parent is a carrier of mild alpha-thalassemia and the other is normal, suggesting that this form of Hb H disease results from the interaction between an inherited defect of alpha-chain production and one member of the pair in chromosome 16 and a new mutation on the other. Restriction-enzyme analysis indicated that the new mutation was not the same in the other three patients, and demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…T he rare association of a-thalassemia and mental retardation (MR) was recognized over 25 years ago by Weatherall and colleagues (Weatherall et al 1981). It was known that athalassemia arises when there is a defect in the synthesis of the a globin chains of adult hemoglobin (HbA, a 2 b 2 ).…”
mentioning
confidence: 99%
“…T he rare association of a-thalassemia and mental retardation (MR) was recognized over 25 years ago by Weatherall and colleagues (Weatherall et al 1981). It was known that athalassemia arises when there is a defect in the synthesis of the a globin chains of adult hemoglobin (HbA, a 2 b 2 ).…”
mentioning
confidence: 99%
“…A TRX was identified when the gene encoding this protein was shown to be mutated in a form of X-linked mental retardation (ATR-X syndrome) in young males (1,2). Furthermore, null mutations in mice are lethal at the embryonic stage of development (3).…”
mentioning
confidence: 99%
“…Alterations in the expression and/or activity of ATRX, both in rodents and humans, result in severe developmental defects, characterized by a number of negative clinical outcomes including psychomotor deficits, cognitive disability, congenital abnormalities, and a-thalassemia (Weatherall et al, 1981). Recent studies have also identified ATRX mutations in a number of cancers, including pancreatic neuroendocrine tumors and glioblastoma multiforme, suggesting that ATRX function is critically important to numerous aspect of cellular homeostasis (Heaphy et al, 2011;Schwartzentruber et al, 2012).…”
Section: Atrx: a Critical Regulator Of Chromatin State And Histone Dymentioning
confidence: 99%